Suspension of voting rights of bankruptcy creditors in the event of a conflict of interest - Rossi Callo, Renzo Rafael (2022)
How should we treat the creditor who votes induced by motives other than maximizing the recovery of his credit? Or to put it another way: how should we treat a creditor who intends to vote in a Meeting of Creditors knowing that what he will lose in the insolvency proceeding will be gained, even more, by another creditor?.The above questions are just some of the questions that the authors resolve in this article, which, based on an interesting case, offers the reader a clear analysis of the conflict of interest of creditors in bankruptcy in the context of creditors’ meetings in bankruptcy matters.As can be seen throughout the text, in the author’s opinion, in the absence of express regulation on this subject in our General Law of the Insolvency System, the statutory limitations or those established in the General Corporations Law on conflicts of interest are transferable. In this sense, the author suggests as an alternative that the suspension of the conflicted creditor’s voting rights be submitted to the consideration of the Meeting of Creditors. However, beyond the solution that is constructed, it is urgent and important to work on an amendment to the General Law of the Insolvency System in order to address this issue.